Place: images, ideas in Salim Barakat Dilshad Novel and Farasikh Alkholod Almahjora as a Model - Seto, Hussain A. (Humanities Journal of University of Zakho, 2017)
The study of the new novel has seen a great place for both critics and readers in the modern era. Therefore, the critical newspapers and magazines have seen a lot of research about the new novel in all its political, psychological and social directions. The readers' reluctance to the traditional style of the novel has a great deal of interference and dominance of the text and its authority; The ruling regime in directing and harnessing the novel text in favor of his power to the writer, and the obligation to enter the documents and decisions that he wants to broadcast through this text, as well as ideological ideas and circulation of these novels. And the novels of Salim Barakat step down as such, he is one of the writers and poets who are referred to as boys, although he was a Kurd, he had the cornerstone of the Arabic language and managed to vocabulary was a great ability, called Arabic and not Arabized by him, and saw him Arab poets by enabling him, Mahmoud Darwish tries not to be affected but influenced by it, and Adonis says: This Kurd has put the Arabic language in his pocket, and he writes the novel in the language of poetry. He has written more than 23 novels, most recently Spaya Sinjar, with a collection of poetry books. The places of Barakat are not arbitrary, but they are systematic in his thinking, through which he searches for his national identity, as well as his place, which lived in some of them and heard about the other. He moves among these places as his home, the image of the place and its significance is reflected in Salim Barakat in its most beautiful form. The place is an integral part of the image of the human when Salim Barakat, and these places have prepared for the reality of rebellion against the reality of marginalization and fragmentation of his country and divided into four parts, trying to waste this place, which shows the reality of the Kurds in their painful reality. And the place at Barakat, a Kurdish political scene talking about the epics experienced by the Kurds in the loss and the oppressions; with those who govern them in these desolate areas, which are manifested in their language and their uneducated names in their non-heritage looted in the time-damaged societies, with a generation tasted bitter by his soldiers in the oblivion of history. He has the awakening of the geographically followed by the awakening of the place in a time when he regains his breath to reach a time that is capable without wasting his identity in this late and alienation that he does not feel. He discovers through the words in his inner self his hidden people, through the memory of the place, for she always keeps the remains of images of the places that have stuck in his memory through the imagination that does not escape his imagination from hearing the memories of those fleeing under the unfair power of the rulers; and his characters part of his place built in his texts feature, where you do not miss personalities took places that are imaginary and appear in the subconscious area in his thinking that he lived in his childhood in his village Mosisana in Qamishlo, remoteness and alienation and persecution in his childhood; he is looking for in these places in the text of the novelist, and mocks his characters to do what deficit is about Todath during the existence of Weary in light of the suffering of his people, who are deprived of their most basic rights; namely, the right of citizenship, where the presence of tens of hundreds of them in villages and cities without identity, and at the time of preparing false civilization they are without identity.